Epigenetic programming, early life nutrition and the risk of metabolic disease. (November 2017) - Block, Tomasz; El-Osta, Assam
Abstract: Time separates the past from the present, during this period memory are formed - written in code and decoded to be read while other memories are erased - but when it comes to the epigenome some memories are harder to forget than others. Recent studies show chemical information is written in the context of the epigenome and codified on histone and non-histone proteins to regulate nuclear processes such as gene transcription. The genome is also subject to modification in the form of 5-methylcytosine, which has been implicated in metabolic memory. In this review, we examine some of the chemical modifications that signal early life events and explore epigenetic changes that underlie the diabetic vasculature. The fine balance between past and present is discussed, as it pertains to gestational diabetes and obesity in context to the Barker hypothesis. We also examine emerging experimental evidence suggesting the hypothalamus as a central regulator of obesity risk and explore current genomic medicine. As for how cells recall specific chemical information, we examine the experimental evidence implicating chemical cues on the epigenome, providing examples of diet during pregnancy and the increased risk of disease in offspring. Graphical abstract: Highlights: Adult health and disease are traced to fetal origins and early life factors. Parental diet regulates epigenetic modification and the risk of metabolic disease in offspring. Nutrient sensing of metabolic status and homeostasis is controlled centrally by the hypothalamus. Hypothalamus interpret extracellular cues to control energy balance by regulating epigenetic information and gene expression.